FAKTOR–FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN BARANG ELEKTRONIK PADA TOKO ANUGERAH DI KEC.BARAKA KAB.ENREKANG - Naidah, Naidah; Hastati, Hastati (Jurnal Ekonomi Balance, 2015)
This study aims to determine whether product quality, service quality, price, and places of purchase decision of Gift Shop and factor analysis most influential in influencing decision of Gift Shop in Kec. Baraka Kab.Enrekang. The population in this study are the consumers of Toko Anugerah. The sample that amounted to 100 respondents using Non-Probability Sampling technique with Accidental sampling approach, that is the technique of determining the sample based on the place, that is who met the researcher if it is suitable. Based on the results of research, obtained regression picture as follows: Y = 0,201 X1 + 0,302 X2 + 0,309 X3 + 0,201 X4 + e. With statistical data analysis, the indicators in this study are valid and the variables are reliable. The independent variables of each of the most influential variables are the variables with regression coefficient of 0.309, then the quality of service with regression coefficient of 0.302, then followed by the most ugly variables namely the correlation coefficient of 0.201, and place variables with coefficients. regression of 0.201. The Gift Shop needs to preserve the elements that already exist well by the customer and need to Install things that are still lacking.